The you I've never known - Hopkins, Ellen (New York : Margaret K. McElderry Books, 2017)
With both joy and fear, seventeen-year-old Ariel begins to explore her sexuality, while living with her controlling, abusive father who has told Ariel that her mother deserted her years ago.
Keywords: Parent and child -- Fiction; Identity -- Fiction; Sexual orientation -- Fiction; Lesbians -- Fiction; Psychopaths -- Fiction; Kidnapping -- Fiction; JUVENILE FICTION / Social Issues / Physical & Emotional Abuse (see also Social Issues / Sexual Abuse).; JUVENILE FICTION / Family / Marriage & Divorce